RhEGF-containing thermosensitive and mucoadhesive polymeric sol–gel for endoscopic treatment of gastric ulcer and bleeding. (March 2014) - Maeng, Jin Hee; So, Jung Won; Kim, Jungju; Kim, In Ae; Jung, Ji Hoon; Min, Kyunghyun; Lee, Don Haeng; Yang, Su-Geun
Gastrointestinal endoscopy is a standard diagnostic tool for gastrointestinal ulcers and cancer. In this study, we have developed recombinant human epidermal growth factor-containing ulcer-coating polymeric sol–gel for endoscopic application. Chitosan and pluronic F127 were employed for their thermoresponsive and bioadhesive properties. At temperatures below 21℃, polymeric sol–gel remains liquid during endoscopic application and transforms to gel at body temperature after application on ulcers. In an in vitro cellular wounding assay, recombinant human epidermal growth factor sol–gel significantly enhanced the cell migration and decreased the wounding area (68%) compared to nontreated, recombinant human epidermal growth factor solution, and sol–gel without recombinant human epidermal growth factor (42, 49, and 32 % decreased at day 1). The in vivo ulcer-healing study was performed in an acetic acid-induced gastric ulcer rat model and proved that our recombinant human epidermal growth factor endoscopic sol–gel facilitated the ulcer-healing process more efficiently than the other treatments. Ulcer sizes in the recombinant human epidermal growth factor sol–gel group were decreased 2.9- and 2.1-fold compared with those in the nontreated group on days 1 and 3 after ulceration, respectively. The mucosal thickness in the recombinant human epidermal growth factor sol–gel group was significantly increased compared to that in the nontreated group (3.2- and 6.9-fold on days 1 and 3 after ulceration, respectively). In a gastric retention study, recombinant human epidermal growth factor sol–gel stayed on the gastric mucosa more than 2 h after application. The present study suggests that recombinant human epidermal growth factor sol–gel is a prospective candidate for treating gastric ulcers via endoscopic application.